Evaluación bioagronómica de ocho cultivares de lechuga iceberg (Lactuca sativa L.), con abonos orgánicos y químicos en el cantón Chambo – provincia de Chimborazo - Oviedo Esparza, Elsa Jimena (2013)
This research was conducted at the El Vergel 5 km from Canton Chambo Chimborazo province. It lasted four months. At an altitude 2672 m The study treatments were eight cultivars of lettuce (Winter T1, T2 Waltz, Bruma T3, T4 Iceland, Patagonia T5, T6 Alpine, Cartagenas T7, T8 Madras). Design We used a randomized complete block design (RCBD) with eight treatments and four replications. To determine differences between treatment means test was used Tukey's multiple range at 95% probability. The best germination percentage was obtained by cultivating Iceland (T4), with 98.23%, and the lower the Winter (T1) with 88.02%. When evaluated the survival percentage of the best percentage is obtained Waltz (T2) and the Alpina (T6) with a mean of 99.31, and the lower the cultivating Haze (T3) with an average of 97.10. The best height of the plant cultivar obtained at 35 days of Iceland (T4), and the lowest in this variable Bruma 3 (T3) to 16.98 cm. The largest number of leaf at 35 days the cultivar Alpine obtained (T6) with 17.70 leaves while the lowest was obtained cultivate Bruma (T3) with 12.42 leaves. The number of days to the formation of the head, the cultivar Winter (T1) with 50, 48 days and fewer days to reach was the Bruma (T3) with 40.00. In days to harvest cultivar Winter (T1) to 77.03 days is the longest slow to be harvested and Bruma (T3) 67.55 days with the least time at late harvest. In the equatorial diameter cultivar that won the largest diameter is Iceland (T4) to 18.75 cm and cultivar Bruma (T3) is the one who got the smallest diameter 15.72 cm. The greater weight of the cabbage cultivar reached Alpine (T6) with 2350.50 g and cultivar that won less weight was Bruma (T3) with 1229.10 g. Cultivar performance was the best performance Alpina (T6) with 47.01 kg and the lowest performing the Mist (T3) to 24.58 kg. The higher return the obtained Alpina xix (T6), and that for every dollar invested will have a profit of 0.64 cents while the other is lower profitability cultivars including having lost in Bruma treatment (T3).